Development and Design of a Remote-Controlled Vannamei Shrimp Feeder - Addhil Izzulhaq; Arif Rakhman; Lukmanul Khakim; Miftakhul Huda (PT. Sentra Ilmiah Teknologi Mandiri, 2026)
Aquaculture pond water commonly supports multiple aquatic species, including seabass and vannamei shrimp. This study specifically concentrates on vannamei shrimp cultivation in pond systems. Feeding management in shrimp aquaculture constitutes a critical operational parameter, as appropriate feed allocation directly influences growth performance, feed conversion efficiency, and overall production yield. This research involved the design and development of an automatic shrimp feeding system utilizing an HX711 load cell weight sensor integrated with a microcontroller-based control unit. Experimental evaluation demonstrated that the Real-Time Clock (RTC) module exhibited a time deviation of approximately one minute slower than the reference time recorded on a laptop. The implementation of the HX711 load cell sensor in the feed container yielded an average measurement error of 3.1% based on a 350-gram calibration test. The system was capable of dispensing feed with a minimum output resolution of 1 gram. Furthermore, operational data generated by the system are transmitted to a database, visualized through a web-based interface, and accessible for real-time monitoring.